Non-selective sodium-ion battery electrolyte applicable to low temperature and preparation method of non-selective sodium-ion battery electrolyte

By using a specific composition of nonaqueous organic solvent system and sodium hexafluorophosphate in sodium ion batteries, the viscosity of the electrolyte and the formation of SEI film are optimized, and the capacity attenuation of sodium ion batteries and SEI films are solved, thereby achieving efficient low-temperature circulation capacity maintenance and stability improvement.

CN119674248APending Publication Date: 2025-03-21彭尚龙
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411416844.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The capacity of sodium ion batteries is severely decayed at low temperatures, and the formation and damage of SEI films lead to a gradual decrease in battery capacity. It is difficult for existing electrolytes to effectively solve these problems.

Method used

A non-aqueous organic solvent system consisting of vinyl carbonate, propylene carbonate, methyl ethyl carbonate, fluorovinyl carbonate and vinyl carbonate are adopted, combined with 1 mol/L of sodium hexafluorophosphate as the sodium salt, and the viscosity of the electrolyte and the formation of the SEI film are optimized by regulating the component ratio and additive content, and the circulation capacity and stability of the battery at low temperatures are improved.

Benefits of technology

It achieves excellent circulation capacity retention rate of sodium ion batteries at low temperatures, improves the low-temperature cycle stability and anti-oxidation performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674248A_ABST
    Figure CN119674248A_ABST
Patent Text Reader

Abstract

The invention discloses a non-selective sodium-ion battery electrolyte suitable for low temperature and a preparation method thereof, and relates to the field of batteries, and the sodium-ion battery electrolyte is composed of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, vinylene carbonate and sodium hexafluorophosphate. The sodium ion battery low-temperature electrolyte with uniform components is obtained by regulating and controlling the proportion of the basic components and mixing the basic components with the additive with proper content, the freezing point of the electrolyte is reduced, the capacity retention ratio of the battery at low temperature is improved, and a new thought is expected to be provided for widening the low-temperature application scene of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion batteries, in particular to a low-temperature, non-selective electrolyte for sodium ion batteries, comprising a non-aqueous organic solvent, a sodium salt and an additive. Background Art

[0002] In the field of electrochemical energy storage, lithium-ion batteries are widely used due to their excellent electrochemical performance. However, my country's lithium resources account for only 5.9% of the world's total, with a high degree of external dependence, long-term foreign regional political risks, and uneven distribution. With the soaring number of electric vehicles and the accelerated development of energy storage equipment, lithium resources are gradually in short supply, and raw material prices are also rising. Lithium-ion batteries alone are not enough to support mankind's full entry into the path of electrification and renewable energy. Sodium-ion batteries have the advantages of abundant raw material resources, low cost, good safety performance, excellent rate performance, and high low-temperature capacity retention. They can effectively reduce my country's dependence on foreign energy storage battery raw materials, solve the raw material problem, and are an important supplement to lithium-ion batteries. The capacity of lithium-ion batteries will decay severely at low temperatures. The desolvation energy of sodium ions during the cycle is lower than that of lithium ions. Therefore, the low-temperature performance of sodium-ion batteries is better than that of lithium-ion batteries. In order for sodium ions to play their advantages at low temperatures, they need to use low-temperature electrolytes with special components and proportions. Therefore, it is necessary to develop an electrolyte suitable for sodium-ion batteries to be used at low temperatures.

[0003] When a sodium-ion battery is charged and activated for the first time, a solid electrolyte interface film (SEI film for short) will be formed on the surface of the negative electrode. The SEI film is an excellent conductor of sodium ions and a good electronic insulator, which can prevent excessive embedding of solvent molecules. However, the SEI film consumes the sodium ions in the positive electrode during its formation, which reduces the first-cycle coulomb efficiency of the sodium-ion battery. In the subsequent cycles, as the SEI film gradually breaks down, it will continue to consume electrolyte and sodium ions, which will cause the capacity of the sodium-ion battery to gradually decay. The solvent structure in the electrolyte will greatly affect the formation process and final structure of the SEI film. Summary of the invention

[0004] The object of the present invention is to provide a non-selective sodium ion battery electrolyte suitable for low temperature and a preparation method thereof, so as to solve the above technical problems.

[0005] The invention discloses a non-selective sodium ion battery electrolyte suitable for use at low temperatures. The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.099% to 4.762% by volume of fluoroethylene carbonate, 0.099% to 4.762% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

[0006] The sodium salt used in the present invention is NaPF6, which is very different from LiFSI in various physical and chemical properties, resulting in different compositions of the SEI film generated on the negative electrode surface during the cycle.

[0007] Furthermore, the sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.1% to 4.5% by volume of fluoroethylene carbonate, 0.1% to 4.5% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

[0008] Furthermore, the freezing point of the ethyl methyl carbonate is -55°C, the viscosity at 25°C is 0.65cp, and the dielectric constant at 25°C is 2.958.

[0009] Furthermore, the sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.5% to 4.0% by volume of fluoroethylene carbonate, 0.5% to 4.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

[0010] Furthermore, the sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 1.0% to 3.0% by volume of fluoroethylene carbonate, 1.0% to 3.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

[0011] Furthermore, the sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 1.0% to 2.0% by volume of fluoroethylene carbonate, 1.0% to 2.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

[0012] The present invention provides a method for preparing a non-selective sodium ion battery electrolyte suitable for low temperature use as follows:

[0013] 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 0.099% to 4.762% by volume of fluoroethylene carbonate, 0.099% to 4.762% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate were weighed and mixed, and stirred evenly to obtain a sodium ion battery electrolyte.

[0014] Furthermore, the stirring conditions are 400 r / min, the temperature is 55° C., and the stirring time is 1 h.

[0015] In the present invention, the electrolyte is firstly changed to have a moderate viscosity (3.18 cp) by changing the component ratio in the electrolyte, so as to ensure that the sodium ion battery has good Na + The conduction rate is then increased by precisely adjusting the additive content to improve the interfacial compatibility between the positive electrode surface and the electrolyte, promoting the formation of a dense SEI film on the negative electrode surface inside the battery, which is beneficial to Na + Rapid deintercalation during the cycle process, due to the strong electronegativity of F in FEC (fluoroethylene carbonate), can effectively reduce the oxidative decomposition of electrolyte components during the charge and discharge process, thereby improving the solvation and desolvation ability of sodium ions in the positive electrode during the battery cycle, and improving its cycle capacity and cycle stability at low temperatures.

[0016] FEC (fluoroethylene carbonate) and VC (vinyl carbonate) are currently reported to be used to prepare membranes. For example, the article "Application of fluoroethylene carbonate in the development of liquid electrolytes for low-temperature lithium-ion batteries" published by Mao Shubiao et al. discloses that organic electrolytes are mainly composed of EC (ethylene carbonate) and PC (propylene carbonate) as solvents, lithium salts such as LiPF6 (lithium hexafluorophosphate) as solutes, and appropriate amounts of additives. In order to improve certain properties of lithium-ion batteries, a small amount of functional additives need to be added. The lithium-ion battery additives that are being researched and developed more include film-forming additives, conductive additives, flame retardant additives, and overcharge-resistant additives. It is for lithium-ion batteries, not sodium-ion batteries, because Na + The Stokes radius in carbonate solvents is smaller than that of Li +, resulting in differences in the influence of solvent composition during the charge and discharge process, making their diffusion speeds different in the same proportion of solvent, and the chemical properties and composition of the electrolyte interface film of the two are also significantly different, which is not suitable for sodium ion batteries. Wang Penglei et al. published "Research on Ethylene Carbonate-based Electrolytes for Lithium Ion Capacitors", which disclosed the use of two kinds of vinyl carbonate electrolytes to make soft-packed lithium ion capacitors (LiCs) based on activated carbon positive electrode and soft carbon negative electrode, and studied the electrochemical properties of the device such as DC internal resistance, rate, impedance and cycle stability. The results show that by adding PC (propylene carbonate) to the mixed solvent of EC (ethylene carbonate) and DEC (diethyl carbonate), LiFSI electrolyte can be obtained, which can make LCs have lower internal resistance and better rate performance, and its electrochemical performance is also significantly improved at low temperature. It also studied the use of lithium ion batteries, and about the combination of EC+PC in the basic electrolyte, it only mentioned that the overall freezing point of the electrolyte is lowered because of the low melting point of PC. It does not involve the effect of EC+PC on electrolyte viscosity and Na + Influence of conductivity. In addition, the EMC (ethyl methyl carbonate) used in the present invention has a freezing point of -55°C, a viscosity of 0.65cp at 25°C, and a dielectric constant of 2.958 at 25°C, which is different from the DMC used in the above invention. Its freezing point is -74°C, the viscosity at 25°C is 0.75cp, and the dielectric constant at 25°C is 2.805. The two have different effects on the freezing point, viscosity and conductivity of the overall electrolyte. In addition, the sodium salt used in the present invention is NaPF6, which is very different from LiFSI in various physical and chemical properties, resulting in different compositions of the SEI film generated on the surface of the negative electrode during the cycle, and therefore different effects on various performances.

[0017] The electrolyte of the present invention is suitable for sodium ion batteries using O3-phase nickel-iron-manganese-based layered oxides and iron-manganese-based Prussian blue analogs as positive electrode materials for stable use at room temperature (30°C) and low temperature (-20°C). In the electrolyte of the present invention, the relative ratio of EC (ethylene carbonate) and PC (propylene carbonate) is precisely controlled to reduce the freezing point and viscosity of the electrolyte while maintaining good electrical conductivity. In addition, by adding a specific proportion of FEC (fluoroethylene carbonate) or VC (vinylene carbonate), because FEC is a single F atom substitution product of EC, and F has a strong electronegativity and weak polarity, therefore, using a suitable addition amount can effectively reduce the freezing point of the electrolyte, improve the antioxidant properties of the electrolyte, and assist in the formation of a dense SEI film at the negative electrode, thereby improving the overall antioxidant stability of the electrolyte and the compatibility of the electrode / electrolyte interface. VC can also promote the formation of the SEI film, and during the cycle process, it can undergo a reduction reaction before the electrolyte, inhibiting the reduction of EC, thereby improving the coulombic efficiency during charging and discharging, and reducing the decomposition and consumption of the electrolyte.

[0018] The present invention has the following beneficial effects:

[0019] The electrolyte of the present invention has a capacity retention rate of 81.53% after 200 cycles when the O3 phase layered oxide is used as the positive electrode material at a temperature of -20°C, and a capacity retention rate of 81.49% after 200 cycles when the Prussian blue analogue is used as the positive electrode material at a temperature of -20°C, both of which show excellent low-temperature performance. The present invention obtains a sodium ion battery low-temperature electrolyte with uniform composition by adjusting the ratio of the basic components and mixing them with an appropriate amount of additives, thereby reducing the freezing point of the electrolyte and improving the capacity retention rate of the battery at low temperatures, which is expected to provide new ideas for broadening the low-temperature application scenarios of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A curve diagram of a battery assembled with a layered oxide positive electrode material using the electrolyte of Comparative Example 1-4 and subjected to 1C constant current cycling at -20°C;

[0021] Figure 2 A graph showing a battery assembled with a layered oxide positive electrode material and the electrolyte of Example 1-6 and subjected to 1C constant current cycling at low temperature (-20°C);

[0022] Figure 3 This is a curve diagram of a battery assembled with a layered oxide positive electrode material using the electrolyte of Example 3 and subjected to 1C constant current cycling at room temperature (30°C);

[0023] Figure 4 The rate test diagram of the battery assembled with the layered oxide positive electrode material using the electrolyte of Example 3 at room temperature (30°C) and low temperature (-20°C);

[0024] Figure 5 The battery assembled with the layered oxide positive electrode material using the electrolyte of Example 3 was subjected to a long cycle test of 400 cycles at 1C;

[0025] Figure 6 The graph is a graph of 1C constant current cycling at room temperature (30°C) and low temperature (-20°C) for a battery assembled with a Prussian blue analogue cathode material as the electrolyte in Example 3;

[0026] Figure 7 The rate test diagram at room temperature (30°C) and low temperature (-20°C) for the battery assembled with the electrolyte of Example 3 and the Prussian blue analogue positive electrode material;

[0027] Figure 8The battery assembled using the electrolyte of Example 3 and a Prussian blue analogue positive electrode material was subjected to a long cycle test of 400 cycles at 1C. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.

[0029] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention but are not intended to limit the present invention.

[0030] Comparative Example 1:

[0031] 1 ml EC (ethylene carbonate), 2 ml PC (propylene carbonate), 7 ml EMC (ethyl methyl carbonate) were measured by volume, and 1.6795 g NaPF6 (sodium hexafluorophosphate) was weighed, mixed, and placed on a magnetic stirrer with a rotation speed of 400 r / min and a table temperature of 55°C, and stirred for 1 hour to obtain an electrolyte;

[0032] Comparative Example 2:

[0033] 1.2 mL of ethylene carbonate, 1.8 mL of propylene carbonate, and 7 mL of ethyl methyl carbonate were weighed according to the volume ratio, and 1.6795 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55°C, and stirred for 1 hour to obtain an electrolyte;

[0034] Comparative Example 3:

[0035] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, and 7 mL of ethyl methyl carbonate were measured by volume, and 1.6795 g of sodium hexafluorophosphate was weighed, mixed, and placed on a magnetic stirrer with a rotation speed of 400 r / min and a table temperature of 55°C, and stirred for 1 hour to obtain an electrolyte;

[0036] Comparative Example 4:

[0037] 2 mL of ethylene carbonate, 1 mL of propylene carbonate, and 7 mL of ethyl methyl carbonate were weighed according to the volume ratio, and 1.6795 g of sodium hexafluorophosphate was weighed, mixed, and placed on a magnetic stirrer with a rotation speed of 400 r / min and a table temperature of 55°C, and stirred for 1 hour to obtain an electrolyte;

[0038] Embodiment 1:

[0039] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.1 mL of vinylene carbonate were weighed according to the volume ratio, and 1.6963 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0040] Embodiment 2:

[0041] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.3 mL of vinylene carbonate were weighed according to the volume ratio, and 1.7299 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0042] Embodiment 3:

[0043] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.5 mL of vinylene carbonate were weighed according to the volume ratio, and 1.7635 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0044] Embodiment 4:

[0045] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.1 mL of fluoroethylene carbonate were weighed according to the volume ratio, and 1.6963 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0046] Embodiment 5:

[0047] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.3 mL of fluoroethylene carbonate were weighed according to the volume ratio, and 1.7299 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0048] Embodiment 6:

[0049] 1.5 mL of ethylene carbonate, 1.5 mL of propylene carbonate, 7 mL of ethyl methyl carbonate, and 0.5 mL of fluoroethylene carbonate were weighed according to the volume ratio, and 1.7635 g of sodium hexafluorophosphate was weighed, mixed, and a magnetic bar was added and placed on a magnetic stirrer at a speed of 400 r / min and a table temperature of 55° C., and stirred for 1 hour to obtain an electrolyte;

[0050] Button cell assembly and electrochemical performance testing:

[0051] The specific technical solution is:

[0052] Layered oxide cathode materials (NaNi 0.33 Fe 0.33 Mn 0.33 O2), an iron-based Prussian blue analogue positive electrode material (Na2Fe[Fe(CN)6]), are mixed and ground with a conductive agent (Super-P) and a binder (polyvinylidene fluoride) in a mass ratio of 8:1:1, and then added into N-methyl-2-pyrrolidone for mixing and grinding. The slurry is then evenly coated on an aluminum foil and vacuum dried at 60°C for 12 hours. Finally, the electrode is pressed with a double roller. Using metallic sodium as the negative electrode, the samples prepared in Comparative Examples 1-4 and Examples 1-6 as the electrolyte, and glass fiber GF / D as the diaphragm, they are assembled into CR2032 button batteries in a glove box filled with argon.

[0053] The charge and discharge cycle test was carried out in a battery testing system (NEWARE CT / CTE-4000 5V 12mA) with a current density of 120mA / g.

[0054] Table (1) shows the viscosity values ​​of Comparative Examples 1-4 and Examples 1-6 at room temperature (30°C) and low temperature (-20°C). It can be seen from the data in the table that in Comparative Examples 1-4 without additives, as the EC content increases, the viscosity of the electrolyte at each temperature also slowly increases. The reason is that the melting point of EC is 36°C, and it is in a solid state at room temperature. Adding EC will significantly increase the viscosity of the electrolyte, but the dielectric constant of EC (25°C) reaches 89.78, which is higher than the dielectric constant of PC (25°C) 64.92, and is a cyclic carbonate co-solvent for sodium ion battery electrolyte with excellent performance. It can significantly reduce the polarization of the battery, improve the battery cycle life and coulomb efficiency, and thus enhance the stability of the electrolyte and the overall performance of the battery. Examples 1-6 are based on Comparative Example 3, with different proportions of FEC and VC added respectively, and a content gradient is set. It can be seen that with the increase of the additive content in the electrolyte, there is an obvious linear relationship between the viscosity of the electrolyte at room temperature (30°C) and (-20°C).

[0055] Table 1 Viscosity at room temperature (30°C) and low temperature (-20°C)

[0056]

[0057]

[0058] Table (2) shows the first cycle capacity and the capacity retention rate after 100 and 200 cycles of button cells assembled in Comparative Examples 1-4 and Examples 1-6 when cycled at 1C current at -20°C. It can be clearly found in Comparative Examples 1-4 that Comparative Example 3 has the highest initial capacity among the four, and the capacity retention rate after 100 and 200 cycles is also in the leading position among the four. Therefore, in subsequent experiments, based on Comparative Example 3, different proportions of FEC and VC were added to obtain Examples 1-6. After addition, it can be clearly observed that the initial capacity of the batteries assembled in Examples 1-6 has decreased to varying degrees. This is because the SEI film generated after addition is more compact, and more inorganic components are consumed compared to Comparative Examples 1-4, but the capacity retention rate has been improved to varying degrees. The reason is that FEC is a single F atom substitution product of EC, and F has a strong electronegativity and weak polarity. Therefore, using a suitable addition amount can effectively reduce the freezing point of the electrolyte, improve the antioxidant performance of the electrolyte, and assist in the formation of a dense SEI film. VC can also promote the formation of SEI film, and can undergo reduction reaction before the electrolyte during the cycle, inhibiting the reduction of EC, and improving the coulombic efficiency and cycle capacity retention rate of the battery.

[0059] Table 2 Battery performance

[0060]

[0061]

[0062] Figures (1) and (2) are curves of the battery assembled with the layered oxide positive electrode material using the electrolyte configured in Comparative Examples 1-4 and Examples 1-6 at -20°C for 1C constant current cycling. As can be seen from the curves in the figure, Comparative Examples 1-4 have basically similar capacity decay rules during the cycle process, with the capacity decreasing rapidly in the first 100 cycles and stabilizing after 100 cycles, but at this time the capacity retention rate is far below 80%, losing its practical value. Therefore, different proportions of FEC and VC are added to Examples 1-3 and Examples 4-6 in Figure (2). It can be seen that Example 1 and Example 4, which added 1% FEC and 1% VC, did not change the trend of rapid battery capacity decay, and as the addition amount increased to 3%, the capacity retention rate of Example 2 and Example 5 showed obvious changes, and the 200-cycle capacity retention rate increased from 17.20% and 24.19% when the addition amount was 1% to 77.45% and 67.84%, respectively. After further increasing the addition amount to 5%, the capacity retention rate of Example 3 increased to 81.53%, while the capacity retention rate of Example 6 decreased to 62.50%. After a series of experiments, it can be seen that the basic electrolyte ratio and additive content in Example 3 are the most suitable, with an initial capacity of 94.99 mAh / g at -20°C, a capacity retention rate of 89.23% after 100 cycles, and a retention rate of 81.53% after 200 cycles, which is the highest among all comparative examples and embodiments.

[0063] Therefore, in the present invention, a cycle test was performed at room temperature (30° C.) on the battery assembled using the layered oxide positive electrode material in Example 3. Figure 3 The results show that the initial capacity of Example 3 is 152.59 mAh / g, the remaining capacity after 200 cycles is 108.17 mAh / g, and the capacity retention rate is 70.8%.

[0064] In order to explore the cycling performance of Example 3 at different current densities, the battery assembled with the layered oxide positive electrode material of Example 3 was subjected to rate tests at 30°C and -20°C. The results are shown in Figure 4 At current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, the capacities at 30°C are 155.9mAh / g, 126.78mAh / g, 115.92mAh / g, 106.76mAh / g, 88.84mAh / g, and 66.17mAh / g, respectively, and the capacities at -20°C are 123.29mAh / g, 110.39mAh / g, 96.43mAh / g, 81.97mAh / g, 71.82mAh / g, and 42.85mAh / g, respectively. This indicates that Example 3 has good rate performance when used as a layered oxide positive electrode material.

[0065] In order to test the long cycle performance of Example 3 at low temperature, the battery assembled with the layered oxide positive electrode material of Example 3 was subjected to a long cycle test of 400 cycles at -20°C and 1C. The results are as follows: Figure 5 , which shows that the remaining capacity after 400 cycles is 71.02 mAh / g and the capacity retention rate is 74.8%, reflecting excellent low-temperature cycle performance.

[0066] In order to demonstrate the non-selectivity of Example 3 of the present invention, the battery assembled with the Prussian blue analog positive electrode material was subjected to 200 cycles of cycling test at -20°C and 30°C at 1C. The results are shown in FIG. Figure 6 At 30°C, the initial capacity is 135.41 mAh / g, and the 200-cycle capacity retention rate is 60.39%. At -20°C, the initial capacity is 111.97 mAh / g, and the 200-cycle capacity retention rate is 81.49%, which also shows excellent low-temperature performance.

[0067] In addition, the battery assembled with the Prussian analogue positive electrode material in Example 3 was also tested at 30°C and -20°C. The results are as follows: Figure 7 , at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, the capacities at 30°C are 126mAh / g, 111.96mAh / g, 104.1mAh / g, 95.14mAh / g, 81.25mAh / g, and 69.27mAh / g, respectively, and the capacities at -20°C are 106.28mAh / g, 96.91mAh / g, 86.59mAh / g, 73.05mAh / g, 65.07mAh / g, and 57.06mAh / g, respectively. This shows that Example 3 also has good rate performance when used as the electrolyte of a battery assembled with a Prussian analogue positive electrode material.

[0068] In order to demonstrate that the battery assembled using the Prussian blue analogue positive electrode material in Example 3 also has good stability at low temperatures, 400 cycles of 1C long cycling were also carried out at -20°C. The results are as follows: Figure 8 The data show that the initial capacity at 1C is 99.54 mAh / g, the remaining capacity after 400 cycles is 77.25 mAh / g, and the capacity retention rate reaches 77.61%. The above three sets of data show that Example 3 can also be applied to Prussian blue analog positive electrode materials, and exhibits good long-cycle stability at -20°C.

[0069] It can be seen that the above best example is embodiment 3, which can provide a sodium ion battery layered oxide positive electrode (NaNi 0.33 Fe 0.33 Mn 0.33O2) and Prussian blue analogue (Na2Fe[Fe(CN)6]) positive electrodes can be used at room temperature (30°C) and low temperature (-20°C) conditions with excellent performance.

Claims

1. A non-selective sodium ion battery electrolyte suitable for low temperature, characterized in that The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.099% to 4.762% by volume of fluoroethylene carbonate, 0.099% to 4.762% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

2. A non-selective sodium ion battery electrolyte suitable for low temperature according to claim 1, characterized in that The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.1% to 4.5% by volume of fluoroethylene carbonate, 0.1% to 4.5% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

3. A non-selective sodium ion battery electrolyte suitable for low temperature according to claim 1 or 2, characterized in that The freezing point of the ethyl methyl carbonate is -53°C, the viscosity at 25°C is 0.65cp, and the dielectric constant at 25°C is 2.

958.

4. A non-selective sodium ion battery electrolyte suitable for low temperature according to claim 1 or 2, characterized in that The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.5% to 4.0% by volume of fluoroethylene carbonate, 0.5% to 4.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

5. A non-selective sodium ion battery electrolyte suitable for low temperature according to claim 4, characterized in that The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 1.0% to 3.0% by volume of fluoroethylene carbonate, 1.0% to 3.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

6. A non-selective sodium ion battery electrolyte suitable for low temperature according to claim 5, characterized in that The sodium ion battery electrolyte is composed of 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 1.0% to 2.0% by volume of fluoroethylene carbonate, 1.0% to 2.0% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate.

7. A method for preparing a non-selective sodium ion battery electrolyte suitable for low temperature as claimed in claim 1, characterized in that The preparation method is as follows: 10% to 20% by volume of ethylene carbonate, 10% to 20% by volume of propylene carbonate, 66.7% to 70% by volume of ethyl methyl carbonate, 0.099% to 4.762% by volume of fluoroethylene carbonate, 0.099% to 4.762% by volume of vinylene carbonate and the balance of 1 mol / L of sodium hexafluorophosphate are weighed and mixed, and after being stirred evenly, a sodium ion battery electrolyte is obtained.

8. The preparation method according to claim 7, characterized in that The stirring conditions were 400 r / min, the temperature was 55°C, and the stirring time was 1 h.

Citation Information

Cited By

  • Low-temperature electrolyte and preparation method and application thereof

    CN120341363A